A method to estimate the transient fluid pressure of a piezoelectric inkjet printer using system dynamic analysis. Issue 6 (17th October 2017) - Wang, Kun; Xi, Juntong
Abstract : Purpose: This paper aims to present a method based on dynamics to find the transient pressure at the nozzle area of a piezoelectric inkjet printer. This pressure responds to input signals of the piezoelectric driver deformation. The pressure at the nozzle is the boundary condition of the computational fluid dynamics model of the inkjet printer nozzle, and serves as the "bridge" between the piezoelectric driver actuation and the droplet generation of an inkjet printer. Design/methodology/approach: The transient pressure was estimated using a fluid-solid coupling numerical model of the printerhead. In this study, a simple step-shape signal was applied. The printerhead chamber was considered to act as a linear Helmholtz resonator to determine the system transfer function between the input of driver deformation and the output of pressure. By decomposing the input signal into several simple signals, the transient pressure is the superposition of those calculated pressures. Findings: The pressure values determined by transfer function and by superposition match the pressure values directly calculated by a fluid-solid coupling model. This demonstrates the rationality and practicability of the method. Originality/value: This paper proposes a method to identify a proper boundary condition of pressure for numerical models that only include the fluid field around the nozzle. This strategy eliminates the need to calculate the complex and unstable fluid-solid coupling for every pattern of input. Additionally, the suitable boundary condition of transient pressure can be set rather than relying on the shape of the PZT driver deformation signal.